2005
DOI: 10.1111/j.0022-1112.2005.00651.x
|View full text |Cite
|
Sign up to set email alerts
|

Ontogenic changes in the allometric scaling of the mass and length relationship in Sprattus sprattus

Abstract: An analysis of mass (M) and standard length (L S ) data for larval, juvenile and adult sprat (Sprattus sprattus; Clupeidae) revealed marked changes in the allometric scaling factor (b in M¼ aL b s ). For sprat <44 mm L S , b was 5Á0, whereas in larger juveniles and adults, b was c. 3Á4 indicating a relatively protracted metamorphic period for this species. # 2005 The Fisheries Society of the British IslesThe mass (M) and length (L) relationship of early life stages of marine fish species has been the subject o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
31
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 9 publications
3
31
0
Order By: Relevance
“…Oscillations in the environmental conditions, especially food supply, may affect the sex ratio among different populations of the same species (Nikolsky, 1978). The observed distinct values of b between the females and males, were coherent with the reports of variations in this parameter for the same fish species related to the age, sex, season and environmental conditions (Le Cren, 1951;Bagenal and Tesch, 1978;Bolger and Connolly, 1989;Goulart, 1994;Godinho, 1997;Morey, et al, 2003;Peck et al, 2005). Usually, b varied from 2.0 to 4.0 (Bagenal and Tesch, 1978).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Oscillations in the environmental conditions, especially food supply, may affect the sex ratio among different populations of the same species (Nikolsky, 1978). The observed distinct values of b between the females and males, were coherent with the reports of variations in this parameter for the same fish species related to the age, sex, season and environmental conditions (Le Cren, 1951;Bagenal and Tesch, 1978;Bolger and Connolly, 1989;Goulart, 1994;Godinho, 1997;Morey, et al, 2003;Peck et al, 2005). Usually, b varied from 2.0 to 4.0 (Bagenal and Tesch, 1978).…”
Section: Discussionsupporting
confidence: 87%
“…Usually, b varied from 2.0 to 4.0 (Bagenal and Tesch, 1978). Although, extreme values could be found, i.e., Peck et al (2005) reported b equal to 5.0 for young of the clupeid Sprattus sprattus. For many fish populations b was close to 3.0 (Ney, 1993) as it was observed for A. paranae in Alagados.…”
Section: Discussionmentioning
confidence: 92%
“…12,no. 1 Tesch 1978, Goulart 1994, Godinho 1997, Peck et al 2005, Nunes & Hartz 2006. The proposed limit values usually vary between 2.5 and 4.0 according to Pope & Kruse (2007) or between 2.0 and 4.0 according to Bagenal & Tesch (1978).…”
Section: Discussionmentioning
confidence: 99%
“…For feeding larvae, the effect of temperature on growth rate (mm day ) using the weight and length of the individual larvae at catch and the allometric length-weight relationship published in Peck et al (2005). A dome-shaped polynomial regression (r 2 = 0.81, optimum growth at 11.9°C, Table 1) was fitted to mean length growth data in relation to in situ temperature (nearest°C).…”
Section: Parameterization Of Vital Ratesmentioning
confidence: 99%
“…The corresponding increase in length was estimated from published length-weight relationships of different size classes of sprat (Peck et al 2005), and its relationship to temperature was best described with a quadratic function (Table 1). YOY stage duration D yoy (d) was then estimated assuming constant growth (mm d -1 ) by dividing the size interval (50 mm) by the growth rate.…”
Section: Parameterization Of Vital Ratesmentioning
confidence: 99%